Production method for smelting molten stainless steel from chromite and recovered converter fly ash
By directly using the use of turntable dust powder and chromium iron ore during the process of smelting stainless steel water water, the problem of low utilization rate and high production costs of transfer furnace dust removal ash is solved, and efficient use and environmental protection methods have been achieved.
Patent Information
- Application Number
- CN202411524682.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, converter dust removal ash has problems of low utilization and high production costs in the process of smelting stainless steel water, and there is no method of chromite or recovery of converter dust removal ash powder.
By directly recycling the dust -dust powder and chromium iron ore, and directly applied during the smelting stainless steel steel water, the solid waste treatment of the dust -dusty ash treatment of the transfer furnace was solved, and the chromium iron alloy consumption was reduced, thereby reducing production costs.
It realizes the efficient utilization of converter dust removal, reduces the consumption of ferrochromium alloy, reduces production costs, and solves the environmental protection problem of solid waste treatment.
Abstract
Description
Technical Field
[0001] The invention relates to an improvement of a stainless steel molten steel smelting process, belonging to the technical field of stainless steel smelting, and specifically to a production method for smelting stainless steel molten steel by using chromite and recovered converter dust. Background Art
[0002] At present, the production method of smelting stainless steel liquid is completed through converter smelting. First, dephosphorized molten iron is added to the converter, and then high-carbon ferrochrome is added in batches. Then, low-carbon ferrochrome is used in the ladle refining furnace for fine-tuning to achieve the adjustment of chromium composition, thereby ensuring that the chromium content in the molten steel meets the requirements of the steel grade. During the converter smelting process, the flue gas dust collected by the dust removal system forms converter dust ash powder, in which the weight percentage of the components is: C: 7%-8%, Fe: 25%-35%, Cr: 8%-16%, calcium oxide: 20%-30%, Si: 1.0%-1.5%, and the remainder is inevitable impurities; this converter dust ash powder is a solid waste, and its composition contains high iron, chromium and other metal oxides. This converter dust ash powder needs to be made into block-shaped converter dust ash through a briquetting process before it can be used. However, if the block-shaped converter dust ash is returned to the furnace for use, the block-shaped converter dust ash is not conducive to smelting reduction, and the utilization rate is low. In addition, the briquetting process will incur high processing and transportation costs, which is not conducive to the control of production costs.
[0003] Chromite ore is the basic raw material for the production of ferrochrome alloy. It contains chromium and iron oxides and other impurities. If an appropriate amount of chromite ore is added to replace part of the high-carbon ferrochrome during the molten steel smelting process, it can not only ensure the quality of the molten steel, but also reduce part of the production cost. After searching, no records were found of chromite ore and recycled converter dust ash powder being used to smelt stainless steel. Summary of the invention
[0004] The object of the present invention is to provide a production method for smelting stainless steel liquid by using chromite and recovered converter dust ash. The converter dust ash powder and chromite directly recovered in the converter smelting process are directly applied to the process of smelting stainless steel liquid, which can not only solve the environmental protection problem of solid waste treatment of converter dust ash, but also reduce the consumption of ferrochrome, thereby reducing the production cost of smelting stainless steel liquid.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is: The production method of using chromite and recovered converter dust to smelt stainless steel liquid is characterized by comprising the following steps: 1. Preparation of raw materials before production and setting of content indicators for the production of stainless steel liquid: sampling of converter dust powder, chromite, high carbon ferrochrome, ferrosilicon alloy, ferromanganese alloy, lime and dolomite to be used for testing and preparation; The converter dust removal ash powder is the converter dust removal ash powder directly collected by the converter dust removal system during the converter smelting process. The calcium oxide in the converter dust removal ash powder exists in the form of slag and does not participate in the molten steel smelting reaction. The carbon content of the converter dust removal ash powder is measured to be ω[C dust removal ash], the chromium content is ω[Cr dust removal ash], the silicon content is ω[Si dust removal ash], and the chromium component recovery rate in the converter dust removal ash powder is ε[Cr dust removal ash]. The block size of the chromite is required to be 20 mm-80 mm; the chromium content of the chromite is measured to be ω[Cr chromite], the carbon content is ω[C chromite], the silicon content is ω[Si chromite], and the chromium component recovery rate in the chromite is ε[Cr chromite]; The block size of the high carbon ferrochrome is required to be 20 mm-80 mm; the chromium content of the high carbon ferrochrome is measured to be ω[Cr high carbon ferrochrome], the carbon content is ω[C high carbon ferrochrome], the silicon content is ω[Si high carbon ferrochrome], and the manganese content is ω[Mn high carbon ferrochrome]; the total addition amount of the high carbon ferrochrome is W[high carbon ferrochrome], and the chromium component recovery rate in the high carbon ferrochrome is ε[Cr high carbon ferrochrome]; The block size of the ferrosilicon alloy is required to be 20 mm-80 mm; the silicon content of the ferrosilicon alloy is measured to be ω[Si ferrosilicon], and the silicon component yield in the ferrosilicon alloy is ε[Si ferrosilicon]; The block size of the ferromanganese alloy is required to be 20 mm-80 mm; the manganese content of the ferromanganese alloy is measured to be ω[Mn ferromanganese], and the manganese component yield in the ferromanganese alloy is ε[Mn ferromanganese]; The effective calcium oxide content of the dolomite is ω[CaO dolomite]; the effective calcium oxide content of the lime is ω[CaO lime]; According to the customer's requirements for stainless steel grades, the chromium content of the finished stainless steel grades is set to ω[finished Cr], the carbon content is ω[finished C], the silicon content is ω[finished Si], the manganese content is ω[finished Mn], the phosphorus content is ω[finished P], and the sulfur content is ω[finished S]; the basicity value of the slag is R; (ii) Adding steel: using a hopper to pour the converter dust powder into the converter, then adding dephosphorized hot metal, and then adding chromite into the converter through a silo; the phosphorus content of the dephosphorized hot metal is ≤0.015%, and the sulfur content is ≤0.04%. The chromium content of the dephosphorized hot metal is measured to be ω[Cr hot metal], the silicon content is ω[Si hot metal], and the carbon content is ω[C hot metal]; the amount of the dephosphorized hot metal added is W[hot metal], the amount of the converter dust powder added is W[dust ash], and the amount of chromite added is W[chromite]; W[dust ash] and W[chromite] are both 2 tons, and the weight ratio of the converter dust powder added, the chromite added, and the dephosphorized hot metal added is 1:1:(25-30); (III) Pre-calculation: The weight of the stainless steel molten steel produced is set as W[molten steel], and the weight of the stainless steel molten steel produced W[molten steel] is the sum of the amount of dephosphorized molten iron added W[molten iron], the amount of converter dust powder added W[dust ash], the amount of chromite added W[chromite] and the amount of high carbon ferrochrome added W[high carbon ferrochrome]; the carbon content in the stainless steel molten steel is set as ω[C molten steel], and the silicon content is set as ω[Si molten steel]; The weight W[molten steel] of the produced stainless steel molten steel, the total amount of high carbon ferrochrome added W[high carbon ferrochrome], the carbon content ω[C molten steel] and the silicon content ω[Si molten steel] in the stainless steel molten steel are calculated according to the following formulas: ω[Cr finished product]×W[molten steel]=W[dust removal ash]×ω[Cr dust removal ash]×ε[Cr dust removal ash]+W[chromite]×ω[Cr chromite]×ε[Cr chromite]+W[high carbon ferrochrome]×ω[Cr high carbon ferrochrome]×ε[Cr high carbon ferrochrome]+W[molten iron]×ω[Cr molten iron]; W[molten steel]=W[molten iron]+W[dust ash]+W[chromite]+W[high carbon ferrochrome]; ω[Cmolten steel] = (W[dust ash] × ω[Cdust ash] + W[chromite] × ω[Cchromite] + W[high carbon ferrochrome] × ω[Chigh carbon ferrochrome] + W[molten iron] × ω[Cmolten iron]) ÷ W[molten steel]; ω[Si molten steel] = (W[dust ash] × ω[Si dust ash] + W[chromite] × ω[Si chromite] + W[high carbon ferrochrome] × ω[Si high carbon ferrochrome] + W[molten iron] × ω[Si molten iron]) ÷ W[molten steel]; The carbon content target of the first-phase blowing molten steel is set to ω[C first-phase target], the amount of oxygen required for the first-phase blowing is set to V[oxygen first-phase], and the oxygen utilization rate of the first-phase blowing is set to η[first-phase]. The amount of oxygen required for the first-phase blowing V[oxygen first-phase] is calculated according to the following formula: V[oxygen phase I] = (ω[C molten steel] - ω[C phase I target]) × W[molten steel] × 1000 × 0.933 ÷ η[phase I] + ω[Si molten steel] × 0.8 × W[molten steel] × 1000; The amount of dolomite added is W[dolomite], W[dolomite] is 0.8 tons; the total amount of lime added in the first phase of blowing is set to W[lime first phase]; the total amount of lime added in the first phase of blowing W[lime first phase] is calculated according to the following formula: W[lime phase I] = 2.14 × ω[Si molten steel] ÷ ω[CaO lime] × R × W[molten steel] - ω[CaO dolomite] × W[dolomite]; (IV) First-stage blowing: The first-stage blowing is started by top-bottom combined blowing. During the blowing process, high-carbon ferrochrome and lime are added into the furnace in batches through the silo, and the dephosphorized molten iron is blown at five oxygen lance positions: During blowing at the first oxygen lance position, 0.8 tons of dolomite is added through the silo. The main function of the dolomite is to protect the converter lining, but the effective calcium oxide component therein will participate in the reaction of the molten steel; the oxygen blowing amount at the first oxygen lance position is 6% of the oxygen amount V[oxygen phase I] required for the first phase of blowing; the high carbon ferrochrome added at the first oxygen lance position is 15% of the total amount of high carbon ferrochrome added W[high carbon ferrochrome]; the lime added at the first oxygen lance position is 15% of the total amount of lime added in the first phase of blowing W[lime phase I]; During blowing at the second oxygen lance position, the oxygen blowing amount at the second oxygen lance position is 40% of the oxygen amount V[oxygen phase I] required for the first phase blowing, the high carbon ferrochrome added at the second oxygen lance position is 50% of the total high carbon ferrochrome added W[high carbon ferrochrome], and the lime added at the second oxygen lance position is 50% of the total lime added in the first phase blowing W[lime phase I]; During blowing at the third oxygen lance position, the oxygen blowing amount at the third oxygen lance position is 30% of the oxygen amount V[oxygen phase I] required for the first phase of blowing, the high carbon ferrochrome added at the third oxygen lance position is 35% of the total high carbon ferrochrome added W[high carbon ferrochrome], and the lime added at the third oxygen lance position is 35% of the total lime added in the first phase of blowing W[lime phase I]; When the fourth oxygen lance is used for blowing, the oxygen blowing amount of the fourth oxygen lance is 16% of the oxygen amount V[oxygen first phase] required for the first phase of blowing; When the fifth oxygen lance is used for blowing, the oxygen blowing amount of the fifth oxygen lance is 8% of the oxygen amount V[oxygen first phase] required for the first phase of blowing; After the blowing is completed, samples are taken for testing, and the carbon content of the first-stage blowing molten steel is measured to be ω[C first-stage test]; (V) Second stage blowing: The second stage blowing is carried out by bottom lance blowing, and lime is added. The amount of lime added in the second stage blowing is W[lime second stage], and the amount of lime added in the second stage blowing W[lime second stage] is 40% of the total amount of lime added in the first stage blowing W[lime first stage]. The amount of oxygen required for the second stage blowing is set to V[oxygen second stage], the oxygen utilization rate of the second stage blowing is set to η[second stage], and the carbon content target of the molten steel for the second stage blowing is set to ω[C second stage target]. The amount of oxygen V[oxygen second stage] required for the second stage blowing is calculated according to the following formula: V[oxygen phase II] = (ω[C phase I detection] - ω[C phase II target]) × W[molten steel] × 1000 × 0.933 ÷ η[phase II]; After the blowing is completed, samples are taken for testing, and the carbon content of the second-stage blowing molten steel is measured as ω [C second-stage test], the silicon content is ω [Si second-stage test], the manganese content is ω [Mn second-stage test], and the chromium content is ω [Cr second-stage test]; (VI) Reduction and tapping: During the reduction period, lime, fluorite, ferrosilicon alloy and ferromanganese alloy are added; the amount of lime added during the reduction period is W[lime reduction]; the amount of fluorite added is 25% of the total amount of lime added in the first stage of blowing W[lime first stage], the amount of lime added in the second stage of blowing W[lime second stage], and the amount of lime added in the reduction period W[lime reduction]; the amount of ferrosilicon alloy added is W[ferrosilicon alloy], and the amount of ferromanganese alloy added is W[ferromanganese alloy]; The amount of lime added during the reduction period W[lime reduction], the amount of ferromanganese alloy added W[ferromanganese alloy] and the amount of ferrosilicon alloy added W[ferrosilicon alloy] are calculated according to the following formula: W[lime reduction]=2.14×{ω[Si molten steel]+(ω[finished Cr product]-ω[Cr second phase detection])×56.1×ω[Si ferrosilicon]÷W[molten steel]}÷ω[CaO lime]×R×W[molten steel]-W[lime first phase]-W[lime second phase]-ω[CaO dolomite]×W[dolomite]; W[ferromanganese alloy]=(ω[Mn finished product]-ω[Mn second-stage test])×W[molten steel]÷ε[Mn ferromanganese]÷ω[Mn ferromanganese]; W[ferrosilicon alloy]=(ω[finished Cr product]-ω[secondary Cr test])×56.1+(ω[finished Si product]-ω[secondary Si test])×W[molten steel]÷ε[Si ferrosilicon]÷ω[Si ferrosilicon]; The molten steel is stirred by blowing argon gas from the bottom, and the reduction time is controlled to be 10 minutes; sampling is performed for testing, and the carbon content of the molten steel after reduction is measured to be ω [C reduction], the silicon content is ω [Si reduction], the manganese content is ω [Mn reduction], and the chromium content is ω [Cr reduction], and the molten steel is poured into a ladle; (VII) Refining: The ladle enters the refining furnace, and under the action of the electrode, 400kg of lime, 200kg of fluorite and 40kg of ferrosilicon powder are added to adjust the slag and temperature; the main function of the ferrosilicon powder and fluorite is to refine and adjust the slag and improve the fluidity of the slag. They react with oxygen in the slag to generate silicon dioxide, and do not react with the molten steel; Use a wire feeder to add 150 meters of calcium wire into the ladle, take samples for testing, and measure the carbon content of the finished molten steel to be ω [C finished product test], silicon content to be ω [Si finished product test], manganese content to be ω [Mn finished product test], chromium content to be ω [Cr finished product test], phosphorus content to be ω [P finished product test], and sulfur content to be ω [S finished product test]; connect the ladle with argon gas for soft blowing, and the soft blowing time is controlled within 10-15 minutes; after the soft blowing is completed, the ladle enters the continuous casting process, and the smelting of molten steel is completed.
[0006] Since there are deviations in the composition and utilization rate of the raw materials used in the above steps, there are deviations between the theoretically calculated values and the actual test results, wherein the deviation between the target value ω[Cfirst-phase target] of the carbon content of the first-phase blowing molten steel and the detected value ω[Cfirst-phase test] of the carbon content of the first-phase blowing molten steel only needs to be within the range of 0% to ±0.05%, and the deviation between the target value ω[Csecond-phase target] of the carbon content of the second-phase blowing molten steel and the detected value ω[Csecond-phase test] of the carbon content of the second-phase blowing molten steel only needs to be within the range of 0% to ±0.005%; the content of each element component in the finished steel product test must be within the range required by the customer for the stainless steel grade.
[0007] The beneficial effect of the present invention is that the converter dust ash powder and chromite directly recovered during the converter smelting process are directly used in the process of smelting stainless steel liquid, which solves the environmental protection problem of solid waste treatment of converter dust ash, reduces the consumption of ferrochrome alloy, and thus reduces the production cost of smelting stainless steel liquid. DETAILED DESCRIPTION
[0008] The production method of using chromite and recovered converter dust to smelt stainless steel liquid is characterized by comprising the following steps: 1. Preparation of raw materials before production and setting of content indicators for the production of stainless steel liquid: sampling of converter dust powder, chromite, high carbon ferrochrome, ferrosilicon alloy, ferromanganese alloy, lime and dolomite to be used for testing and preparation; The converter dust removal ash powder is a converter dust removal ash powder directly collected by a converter dust removal system during the converter smelting process; the weight percentage of the components thereof is: C: 7%-8%, Fe: 25%-35%, Cr: 8%-16%, calcium oxide: 20%-30%, Si: 1.0%-1.5%, and the remainder is unavoidable impurities; the carbon content of the converter dust removal ash powder is measured to be ω[C dust removal ash], the chromium content is ω[Cr dust removal ash], the silicon content is ω[Si dust removal ash], and the chromium component recovery rate in the converter dust removal ash powder is ε[Cr dust removal ash]; The block size of the chromite is required to be 20 mm-80 mm, and the weight percentage of its components is: Fe: 30%-40%, C: 6%-8%, Si: 1%-5%, Cr: 35%-45%; the chromium content of the chromite is measured to be ω[Cr chromite], the carbon content is ω[C chromite], the silicon content is ω[Si chromite], and the chromium component recovery rate in the chromite is ε[Cr chromite]. The block size of the high carbon ferrochrome is required to be 20mm-80mm, and the weight percentage of its components is: Fe: 30%-40%, Cr: 50%-55%, C: 7%-8%, Si: 2%-6%, Mn: 0.2%-0.4%, and the remainder is inevitable impurities; the chromium content of the high carbon ferrochrome is measured to be ω[Cr high carbon ferrochrome], the carbon content is ω[C high carbon ferrochrome], the silicon content is ω[Si high carbon ferrochrome], and the manganese content is ω[Mn high carbon ferrochrome]; the total addition amount of the high carbon ferrochrome is W[high carbon ferrochrome], and the chromium component recovery rate in the high carbon ferrochrome is ε[Cr high carbon ferrochrome]; The block size of the ferrosilicon alloy is required to be 20 mm-80 mm, and the silicon content is 65%-75%; the silicon content of the ferrosilicon alloy is measured to be ω[Si ferrosilicon], and the silicon component yield in the ferrosilicon alloy is ε[Si ferrosilicon]; The block size of the ferromanganese alloy is required to be 20 mm-80 mm, and the manganese content is 62%-68%; the manganese content of the ferromanganese alloy is measured to be ω[Mn ferromanganese], and the manganese component recovery rate in the ferromanganese alloy is ε[Mn ferromanganese]; The effective calcium oxide content of the dolomite is ω[CaO dolomite]; the effective calcium oxide content of the lime is ω[CaO lime]; According to the customer's requirements for stainless steel grades, the chromium content of the finished stainless steel grades is set to ω[finished Cr], the carbon content is ω[finished C], the silicon content is ω[finished Si], the manganese content is ω[finished Mn], the phosphorus content is ω[finished P], and the sulfur content is ω[finished S]; the basicity value of the slag is R; (ii) Adding steel: using a hopper to pour the converter dust powder into the converter, then adding dephosphorized hot metal, and then adding chromite into the converter through a silo; the phosphorus content of the dephosphorized hot metal is ≤0.015%, and the sulfur content is ≤0.04%. The chromium content of the dephosphorized hot metal is measured to be ω[Cr hot metal], the silicon content is ω[Si hot metal], and the carbon content is ω[C hot metal]; the amount of the dephosphorized hot metal added is W[hot metal], the amount of the converter dust powder added is W[dust ash], and the amount of chromite added is W[chromite]; W[dust ash] and W[chromite] are both 2 tons, and the weight ratio of the converter dust powder added, the chromite added, and the dephosphorized hot metal added is 1:1:(25-30); (III) Pre-calculation: The weight of the stainless steel molten steel produced is set as W[molten steel], and the weight of the stainless steel molten steel produced W[molten steel] is the sum of the amount of dephosphorized molten iron added W[molten iron], the amount of converter dust powder added W[dust ash], the amount of chromite added W[chromite] and the amount of high carbon ferrochrome added W[high carbon ferrochrome]; the carbon content in the stainless steel molten steel is set as ω[C molten steel], and the silicon content is set as ω[Si molten steel]; The weight W[molten steel] of the produced stainless steel molten steel, the total amount of high carbon ferrochrome added W[high carbon ferrochrome], the carbon content ω[C molten steel] and the silicon content ω[Si molten steel] in the stainless steel molten steel are calculated according to the following formulas: Formula 1: ω[Cr finished product]×W[molten steel]=W[dust ash]×ω[Cr dust ash]×ε[Cr dust ash]+W[chromite]×ω[Cr chromite]×ε[Cr chromite]+W[high carbon ferrochrome]×ω[Cr high carbon ferrochrome]×ε[Cr high carbon ferrochrome]+W[molten iron]×ω[Cr molten iron]; Formula 2: W[molten steel]=W[molten iron]+W[dust ash]+W[chromite]+W[high carbon ferrochrome]; Formula 3: ω[Cmolten steel] = (W[dust ash] × ω[Cdust ash] + W[chromite] × ω[Cchromite] + W[high carbon ferrochrome] × ω[Chigh carbon ferrochrome] + W[molten iron] × ω[Cmolten iron]) ÷ W[molten steel]; Formula 4: ω[Si molten steel] = (W[dust ash] × ω[Si dust ash] + W[chromite] × ω[Si chromite] + W[high carbon ferrochrome] × ω[Si high carbon ferrochrome] + W[molten iron] × ω[Si molten iron]) ÷ W[molten steel]; The carbon content target of the first-phase blowing molten steel is set to ω[C first-phase target], the amount of oxygen required for the first-phase blowing is set to V[oxygen first-phase], and the oxygen utilization rate of the first-phase blowing is set to η[first-phase]. The amount of oxygen required for the first-phase blowing V[oxygen first-phase] is calculated according to the following formula: Formula 5: V[oxygen phase I] = (ω[C molten steel] - ω[C phase I target]) × W[molten steel] × 1000 × 0.933 ÷ η[phase I] + ω[Si molten steel] × 0.8 × W[molten steel] × 1000; The amount of dolomite added is W[dolomite], W[dolomite] is 0.8 tons; the total amount of lime added in the first phase of blowing is set to W[lime first phase]; the total amount of lime added in the first phase of blowing W[lime first phase] is calculated according to the following formula: Formula 6: W[lime phase I] = 2.14×ω[Si molten steel]÷ω[CaO lime]×R×W[molten steel]-ω[CaO dolomite]×W[dolomite]; (IV) First-stage blowing: The first-stage blowing is started by top-bottom combined blowing. During the blowing process, high-carbon ferrochrome and lime are added into the furnace in batches through the silo, and the dephosphorized molten iron is blown at five oxygen lance positions: During blowing at the first oxygen lance position, 0.8 tons of dolomite is added through the silo; the oxygen blowing amount at the first oxygen lance position is 6% of the oxygen amount V[oxygen phase I] required for the first phase of blowing; the high carbon ferrochrome added at the first oxygen lance position is 15% of the total amount of high carbon ferrochrome added W[high carbon ferrochrome]; the lime added at the first oxygen lance position is 15% of the total amount of lime added in the first phase of blowing W[lime phase I]; During blowing at the second oxygen lance position, the oxygen blowing amount at the second oxygen lance position is 40% of the oxygen amount V[oxygen phase I] required for the first phase blowing, the high carbon ferrochrome added at the second oxygen lance position is 50% of the total high carbon ferrochrome added W[high carbon ferrochrome], and the lime added at the second oxygen lance position is 50% of the total lime added in the first phase blowing W[lime phase I]; During blowing at the third oxygen lance position, the oxygen blowing amount at the third oxygen lance position is 30% of the oxygen amount V[oxygen phase I] required for the first phase of blowing, the high carbon ferrochrome added at the third oxygen lance position is 35% of the total high carbon ferrochrome added W[high carbon ferrochrome], and the lime added at the third oxygen lance position is 35% of the total lime added in the first phase of blowing W[lime phase I]; When the fourth oxygen lance is used for blowing, the oxygen blowing amount of the fourth oxygen lance is 16% of the oxygen amount V[oxygen first phase] required for the first phase of blowing; When the fifth oxygen lance is used for blowing, the oxygen blowing amount of the fifth oxygen lance is 8% of the oxygen amount V[oxygen first phase] required for the first phase of blowing; After the blowing is completed, samples are taken for testing, and the carbon content of the first-stage blowing molten steel is measured to be ω[C first-stage test]; (V) Second stage blowing: The second stage blowing is carried out by bottom lance blowing, and lime is added. The amount of lime added in the second stage blowing is W[lime second stage], and the amount of lime added in the second stage blowing W[lime second stage] is 40% of the total amount of lime added in the first stage blowing W[lime first stage]. The amount of oxygen required for the second stage blowing is set to V[oxygen second stage], the oxygen utilization rate of the second stage blowing is set to η[second stage], and the carbon content target of the molten steel for the second stage blowing is set to ω[C second stage target]. The amount of oxygen V[oxygen second stage] required for the second stage blowing is calculated according to the following formula: Formula 7: V[oxygen phase II] = (ω[C phase I detection] - ω[C phase II target]) × W[molten steel] × 1000 × 0.933 ÷ η[phase II]; After the blowing is completed, samples are taken for testing, and the carbon content of the second-stage blowing molten steel is measured as ω [C second-stage test], the silicon content is ω [Si second-stage test], the manganese content is ω [Mn second-stage test], and the chromium content is ω [Cr second-stage test]; (VI) Reduction and tapping: During the reduction period, lime, fluorite, ferrosilicon alloy and ferromanganese alloy are added; the amount of lime added during the reduction period is W[lime reduction]; the amount of fluorite added is 25% of the total amount of lime added in the first stage of blowing W[lime first stage], the amount of lime added in the second stage of blowing W[lime second stage], and the amount of lime added in the reduction period W[lime reduction]; the amount of ferrosilicon alloy added is W[ferrosilicon alloy], and the amount of ferromanganese alloy added is W[ferromanganese alloy]; The amount of lime added during the reduction period W[lime reduction], the amount of ferromanganese alloy added W[ferromanganese alloy] and the amount of ferrosilicon alloy added W[ferrosilicon alloy] are calculated according to the following formula: Formula 8: W[lime reduction]=2.14×{ω[Si molten steel]+(ω[Cr finished product]-ω[Cr second phase detection])×56.1×ω[Si ferrosilicon]÷W[molten steel]}÷ω[CaO lime]×R×W[molten steel]-W[lime first phase]-W[lime second phase]-ω[CaO dolomite]×W[dolomite]; Formula 9: W[ferromanganese alloy] = (ω[Mn finished product] - ω[Mn second-stage test]) × W[molten steel] ÷ ε[Mn ferromanganese] ÷ ω[Mn ferromanganese]; Formula 10: W[ferrosilicon alloy] = (ω[finished Cr product] - ω[secondary Cr test]) × 56.1 + (ω[finished Si product] - ω[secondary Si test]) × W[molten steel] ÷ ε[Si ferrosilicon] ÷ ω[Si ferrosilicon]; The molten steel is stirred by blowing argon gas from the bottom, and the reduction time is controlled to be 10 minutes; sampling is performed for testing, and the carbon content of the molten steel after reduction is measured to be ω [C reduction], the silicon content is ω [Si reduction], the manganese content is ω [Mn reduction], and the chromium content is ω [Cr reduction], and the molten steel is poured into a ladle; (VII) Refining: The ladle enters the refining furnace, and under the action of the electrode, 400kg of lime, 200kg of fluorite and 40kg of ferrosilicon powder are added to adjust the slag and temperature; Use a wire feeder to add 150 meters of calcium wire into the ladle, take samples for testing, and measure the carbon content of the finished molten steel to be ω [C finished product test], silicon content to be ω [Si finished product test], manganese content to be ω [Mn finished product test], chromium content to be ω [Cr finished product test], phosphorus content to be ω [P finished product test], and sulfur content to be ω [S finished product test]; connect the ladle with argon gas for soft blowing, and the soft blowing time is controlled within 10-15 minutes; after the soft blowing is completed, the ladle enters the continuous casting process, and the smelting of molten steel is completed.
[0009] Since there are deviations in the composition and utilization rate of the raw materials used in the above steps, there are deviations between the theoretically calculated values and the actual test results, wherein the deviation between the target value ω[Cfirst-phase target] of the carbon content of the first-phase blowing molten steel and the detected value ω[Cfirst-phase test] of the carbon content of the first-phase blowing molten steel only needs to be within the range of 0% to ±0.05%, and the deviation between the target value ω[Csecond-phase target] of the carbon content of the second-phase blowing molten steel and the detected value ω[Csecond-phase test] of the carbon content of the second-phase blowing molten steel only needs to be within the range of 0% to ±0.005%; the content of each element component in the finished steel product test must be within the range required by the customer for the stainless steel grade. Embodiment 1:
[0010] The parameters of stainless steel required by the customer are: C: 0.03%-0.05%, Si: 0.2%-0.5%, Mn: 0.3%-0.5%, P: 0%-0.035%, S: 0-0.006%, Cr: 16%-18%.
[0011] The production method of using chromite and recovered converter dust to smelt stainless steel liquid is carried out according to the above steps, wherein: In step (a): After testing, the weight percentage of the components of the converter dust removal ash powder is: Fe: 35%, calcium oxide: 30%, carbon content ω[C dust removal ash] is 7%, chromium content ω[Cr dust removal ash] is 8%, silicon content ω[Si dust removal ash] is 1%, and the balance is inevitable impurities; the chromium component recovery rate ε[Cr dust removal ash] in the converter dust removal ash powder is 80%; The block size of the chromite is 20mm-80mm. After testing, the weight percentage of its components is as follows: iron content is 40%, chromium content ω[Cr chromite] is 35%, carbon content ω[C chromite] is 6%, silicon content ω[Si chromite] is 1%; the chromium component recovery rate ε[Cr chromite] in the chromite is 90%; After testing, the block size of the high carbon ferrochrome is 20mm-80mm, and the weight percentage of its components is: iron content 40%, chromium content ω[Cr high carbon ferrochrome] is 50%, carbon content ω[C high carbon ferrochrome] is 7%, silicon content ω[Si high carbon ferrochrome] is 2%, manganese content ω[Mn high carbon ferrochrome] is 0.2%, and the remainder is inevitable impurities; the total addition amount of the high carbon ferrochrome is W[high carbon ferrochrome], and the chromium component recovery rate ε[Cr high carbon ferrochrome] in the high carbon ferrochrome is 95%; The block size of the ferrosilicon alloy is 20 mm-80 mm. After testing, the silicon content ω[Si ferrosilicon] of the ferrosilicon alloy is 65%, and the silicon component yield ε[Si ferrosilicon] in the ferrosilicon alloy is 75%; The block size of the ferromanganese alloy is 20 mm to 80 mm. After testing, the manganese content ω [Mn ferromanganese] of the ferromanganese alloy is 62%, and the manganese component recovery rate ε [Mn ferromanganese] in the ferromanganese alloy is 99%; After testing, the effective calcium oxide content ω[CaO dolomite] of the dolomite is 32%; the effective calcium oxide content ω[CaO lime] of the lime is 93%; According to the customer's requirements for stainless steel grades, the chromium content ω[Cr finished product] of the produced stainless steel grade is set to 16%, the carbon content ω[C finished product] is set to 0.03%, the silicon content ω[Si finished product] is set to 0.2%, the manganese content ω[Mn finished product] is set to 0.3%, the phosphorus content ω[P finished product] does not exceed 0.035%, and the sulfur content ω[S finished product] does not exceed 0.005%; the slag basicity value R is 2.2; at the same time, the weight of the produced stainless steel molten steel is set to W[molten steel], the carbon content in the stainless steel molten steel is set to ω[C molten steel], and the silicon content is set to ω[Si molten steel]; In step (ii): After testing, the phosphorus content of the dephosphorized molten iron is 0.01%, the sulfur content is 0.01%, the silicon content ω[Si molten iron] is 0%, the chromium content ω[Cr molten iron] is 0%, and the carbon content ω[C molten iron] is 3.1%; the amount of the dephosphorized molten iron added W[molten iron] is 50 tons, the amount of the converter dust ash powder added W[dust ash] is 2 tons, and the amount of chromite added W[chromite] is 2 tons; W[dust ash]: W[chromite]: W[molten iron] is 1:1:25; In step (3), substitute the formula and calculate: Formula 1: 16%×W[molten steel]=2×8%×80%+2×35%×90%+W[high carbon ferrochrome]×50%×95%+50×0; Formula 2: W[molten steel]=50+2+2+W[high carbon ferrochrome]; Calculation: W [high carbon ferrochrome] = 25.02 tons; W [molten steel] = 79.02 tons; Formula 3: ω[C molten steel] = (2×7% + 2×6% + 25.02×7% + 50×3.1%) ÷ 79.02; calculated: ω[C molten steel] = 4.51%; Formula 4: ω[Si molten steel]=(2×1%+2×1%+25.02×2%+50×0)÷79.02; calculated: ω[Si molten steel]=0.68%; The weight of the stainless steel molten steel produced W[molten steel] is 79.02 tons, the carbon content of the stainless steel molten steel is ω[C molten steel] is 4.51%, and the silicon content ω[Si molten steel] is 0.68%; the total amount of high carbon ferrochrome added W[high carbon ferrochrome] is 25.02 tons; Set the carbon content target ω[C1st phase target] of the first phase blowing molten steel to 0.35%, and the oxygen utilization rate η[1st phase] of the first phase blowing to 65%; substitute into the formula and calculate, Formula 5: V[oxygen phase I] = (4.51% - 0.35%) × 79.02 × 1000 × 0.933 ÷ 65% + 0.68% × 0.8 × 79.02 × 1000; calculated: V[oxygen phase I] = 5148.31 cubic meters; the amount of oxygen V[oxygen phase I] required for the first phase blowing is 5148.31 cubic meters; The amount of dolomite added W[dolomite] is 0.8 tons; substitute into the formula and calculate, Formula 6: W[lime phase I]=2.14×0.68%÷93%×2.2×79.02-32%×0.8; calculated: W[lime phase I]=2.46 tons; the total amount of lime added in the first phase blowing W[lime phase I] is 2.46 tons; In step (iv): During blowing at the first oxygen lance position, the oxygen blowing volume at the first oxygen lance position was 308.90 cubic meters, the amount of high carbon ferrochrome added was 3.75 tons, and the amount of lime added was 0.37 tons; When the second oxygen lance position is used for blowing, the oxygen blowing volume of the second oxygen lance position is 2059.32 cubic meters, the amount of high carbon ferrochrome added is 12.51 tons, and the amount of lime added is 1.23 tons; When the third oxygen lance position was used for blowing, the oxygen blowing volume of the third oxygen lance position was 1544.49 cubic meters, the amount of high carbon ferrochrome added was 8.76 tons, and the amount of lime added was 0.86 tons; When the fourth oxygen lance position is blowing, the oxygen blowing volume of the fourth oxygen lance position is 823.73 cubic meters; When the fifth oxygen lance position is blowing, the oxygen blowing volume of the fifth oxygen lance position is 411.86 cubic meters; After the blowing was completed, samples were taken for testing, and the carbon content of the first-stage blowing molten steel was measured to be 0.36% [C first-stage test]. In step (V): The amount of lime added in the second stage blowing W[lime second stage] is W[lime first stage]×40%=2.46×40%=0.98 tons; Set the carbon content target ω[C2nd phase target] of the second phase blowing molten steel to 0.02%, and the oxygen utilization rate η[2nd phase] of the second phase blowing to 20%; substitute into the formula and calculate, Formula 7: V[oxygen phase II] = (0.36% - 0.02%) × 79.02 × 1000 × 0.933 ÷ 20%; calculated: V[oxygen phase II] = 1253.34 cubic meters; The amount of oxygen V[oxygen phase II] required for the second phase blowing is 1253.34 cubic meters; After the blowing was completed, samples were taken for testing, and the carbon content ω[C second phase test] of the second phase blowing molten steel was 0.022%, the silicon content ω[Si second phase test] was 0.01%, the manganese content ω[Mn second phase test] was 0.05%, and the chromium content ω[Cr second phase test] was 13.8%; In step (six), substitute the formula and calculate: Formula 8: W[lime reduction]=2.14×{0.68%+(16%-13.8%)×56.1×65%÷79.02}÷93%×2.2×79.02-2.46-0.98-32%×0.8; calculated: W[lime reduction]=3.09 tons; the amount of lime added during the reduction period W[lime reduction] is 3.09 tons; The amount of fluorite added is (W[lime phase I]+W[lime phase II]+W[lime reduction])×25%=(2.46+0.98+3.09)×25%=1.63 tons; the amount of fluorite added is 1.63 tons; Formula 9: W[ferromanganese alloy]=(0.3%-0.05%)×79.02÷99%÷62%; calculated: W[ferromanganese alloy]=0.32 tons; Formula 10: W[ferrosilicon alloy]=(16%-13.8%)×56.1+(0.2%-0.01%)×79.02÷75%÷65%; calculated: W[ferrosilicon alloy]=1.54 tons; The amount of ferromanganese alloy added W[ferromanganese alloy] is 0.32 tons; the amount of ferrosilicon alloy added W[ferrosilicon alloy] is 1.54 tons; The molten steel was stirred by blowing argon gas from the bottom, and the reduction time was 10 minutes; sampling and testing, the carbon content ω[C reduction] of the molten steel after reduction was measured to be 0.029%, the silicon content ω[Si reduction] was 0.21%, the manganese content ω[Mn reduction] was 0.32%, and the chromium content ω[Cr reduction] was 16.02%, and the molten steel was poured into a ladle; In step (seven): After adding calcium wire into the ladle, sampling and testing were carried out, and the carbon content ω[C finished product detection] of the finished molten steel was measured to be 0.031%, the silicon content ω[Si finished product detection] was 0.20%, the manganese content ω[Mn finished product detection] was 0.31%, the chromium content ω[Cr finished product detection] was 16.01%, the phosphorus content ω[P finished product detection] was 0.018%, and the sulfur content ω[S finished product detection] was 0.002%; the argon gas in the ladle was connected for soft blowing, the soft blowing time was 10 minutes, and the smelting was completed.
[0012] In the above steps, the deviation value of the carbon content target value ω[C1st phase target] of the first-phase blowing molten steel and the carbon content detection value ω[C1st phase detection] of the first-phase blowing molten steel is 0.01%, which meets the deviation value range requirement of 0% to ±0.05%; the deviation value of the carbon content target value ω[C2nd phase target] of the second-phase blowing molten steel and the carbon content detection value ω[C2nd phase detection] of the second-phase blowing molten steel is 0.002%, which meets the deviation value range requirement of 0% to ±0.005%; the content of each element component of the finished molten steel product detection is within the steel grade parameter range required by the customer. Embodiment 2:
[0013] The parameters of stainless steel required by the customer are: C: 0.03%-0.05%, Si: 0.2%-0.5%, Mn: 0.3%-0.5%, P: 0%-0.035%, S: 0-0.006%, Cr: 16%-18%.
[0014] The production method of using chromite and recovered converter dust to smelt stainless steel liquid is carried out according to the above steps, wherein: In step (a): After testing, the weight percentage of the components of the converter dust ash powder is: Fe: 30%, calcium oxide: 25%, carbon content ω[C dust ash] is 7.5%, chromium content ω[Cr dust ash] is 12%, silicon content ω[Si dust ash] is 1.25%, and the balance is inevitable impurities; the chromium component recovery rate ε[Cr dust ash] in the converter dust ash powder is 80%; The block size of the chromite is 20mm-80mm. After testing, the weight percentage of its components is as follows: iron content is 35%, chromium content ω[Cr chromite] is 40%, carbon content ω[C chromite] is 7%, silicon content ω[Si chromite] is 3%; the chromium component recovery rate ε[Cr chromite] in the chromite is 90%; After testing, the block size of the high carbon ferrochrome is 20mm-80mm, and the weight percentage of its components is: iron content 35%, chromium content ω[Cr high carbon ferrochrome] is 53%, carbon content ω[C high carbon ferrochrome] is 7.5%, silicon content ω[Si high carbon ferrochrome] is 4%, manganese content ω[Mn high carbon ferrochrome] is 0.3%, and the rest is inevitable impurities; the chromium component recovery rate ε[Cr high carbon ferrochrome] in the high carbon ferrochrome is 95%; The block size of the ferrosilicon alloy is 20 mm-80 mm. After testing, the silicon content ω[Si ferrosilicon] of the ferrosilicon alloy is 70%, and the silicon component yield ε[Si ferrosilicon] in the ferrosilicon alloy is 75%; The block size of the ferromanganese alloy is 20 mm to 80 mm. After testing, the manganese content ω [Mn ferromanganese] of the ferromanganese alloy is 65%, and the manganese component recovery rate ε [Mn ferromanganese] in the ferromanganese alloy is 99%; After testing, the effective calcium oxide content ω[CaO dolomite] of the dolomite is 32%; the effective calcium oxide content ω[CaO lime] of the lime is 93%; According to the customer's requirements for stainless steel grades, the chromium content ω[Cr finished product] of the produced stainless steel grade is set to 17%, the carbon content ω[C finished product] is set to 0.04%, the silicon content ω[Si finished product] is set to 0.35%, the manganese content ω[Mn finished product] is set to 0.4%, the phosphorus content ω[P finished product] does not exceed 0.035%, and the sulfur content ω[S finished product] does not exceed 0.005%; the slag basicity value R is 2.2; at the same time, the weight of the produced stainless steel molten steel is set to W[molten steel], the carbon content in the stainless steel molten steel is set to ω[C molten steel], and the silicon content is set to ω[Si molten steel]; In step (ii): After testing, the phosphorus content of the dephosphorized molten iron is 0.015%, the sulfur content is 0.02%, the silicon content ω[Si molten iron] is 0%, the chromium content ω[Cr molten iron] is 0%, and the carbon content ω[C molten iron] is 3.3%; the amount of the dephosphorized molten iron added W[molten iron] is 55 tons, the amount of the converter dust ash powder added W[dust ash] is 2 tons, and the amount of chromite added W[chromite] is 2 tons; W[dust ash]: W[chromite]: W[molten iron] is 1:1:27.5; In step (3): Substitute the formula and calculate: Formula 1: 17%×W[molten steel]=2×12%×80%+2×40%×90%+W[high carbon ferrochrome]×53%×95%+50×0; Formula 2: W[molten steel]=55+2+2+W[high carbon ferrochrome]; Calculation: W[high carbon ferrochrome]=27.34 tons; W[molten steel]=86.34 tons; Formula 3: ω[C molten steel] = (2×7.5%+2×7%+27.34×7.5%+55×3.3%)÷86.34; calculated: ω[C molten steel] = 4.81%; Formula 4: ω[Si molten steel]=(2×1.25%+2×3%+27.34×4%+55×0)÷86.34; calculated: ω[Si molten steel]=1.37%; The weight of the stainless steel molten steel produced W[molten steel] is 86.34 tons, the carbon content of the stainless steel molten steel is ω[C molten steel] is 4.81%, and the silicon content ω[Si molten steel] is 1.37%; the total amount of high carbon ferrochrome added W[high carbon ferrochrome] is 27.34 tons; The carbon content target ω[C1st phase target] of the first phase blowing molten steel is set to 0.35%, and the oxygen utilization rate η[1st phase] of the first phase blowing is set to 65%; substitute into the formula and calculate: Formula 5: V[oxygen phase I] = (4.81% - 0.35%) × 86.34 × 1000 × 0.933 ÷ 65% + 1.37% × 0.8 × 86.34 × 1000; calculated: V[oxygen phase I] = 6473.61 cubic meters; The amount of oxygen V[oxygen phase I] required for the first phase of blowing is 6473.61 cubic meters; The amount of dolomite added W [dolomite] is 0.8 tons; substitute into the formula and calculate: Formula 6: W[lime phase I] = 2.14 × 1.37% ÷ 93% × 2.2 × 86.34 - 32% × 0.8; calculated: W[lime phase I] = 5.73 tons; The total amount of lime added in the first phase of blowing W[lime phase I] is 5.73 tons; In step (iv): During blowing at the first oxygen lance position, the oxygen blowing volume at the first oxygen lance position was 388.42 cubic meters, the amount of high carbon ferrochrome added was 4.10 tons, and the amount of lime added was 0.86 tons; During blowing at the second oxygen lance position, the oxygen blowing volume at the second oxygen lance position was 2589.44 cubic meters, the amount of high carbon ferrochrome added was 13.67 tons, and the amount of lime added was 2.87 tons; When the third oxygen lance position was used for blowing, the oxygen blowing volume of the third oxygen lance position was 1942.08 cubic meters, the amount of high carbon ferrochrome added was 9.57 tons, and the amount of lime added was 2.01 tons; When the fourth oxygen lance position is blowing, the oxygen blowing volume of the fourth oxygen lance position is 1035.78 cubic meters; When the fifth oxygen lance position is blowing, the oxygen blowing volume of the fifth oxygen lance position is 517.89 cubic meters; After the blowing was completed, samples were taken for testing, and the carbon content of the first-stage blowing molten steel was measured to be 0.35% [C first-stage test]. In step (V): The amount of lime added in the second stage blowing is W[lime second stage]=5.73×40%=2.29 tons; Set the carbon content target ω[C2nd phase target] of the second phase blowing molten steel to 0.03% and the oxygen utilization rate η[2nd phase] of the second phase blowing to 20%; substitute into the formula and calculate: Formula 7: V[oxygen phase II] = (0.35% - 0.03%) × 86.34 × 1000 × 0.933 ÷ 20%; calculated: V[oxygen phase II] = 1288.88 cubic meters; The amount of oxygen V[oxygen phase II] required for the second phase blowing is 1288.88 cubic meters; After the blowing was completed, samples were taken for testing, and the carbon content ω[C second phase test] of the second phase blowing molten steel was 0.03%, the silicon content ω[Si second phase test] was 0.02%, the manganese content ω[Mn second phase test] was 0.09%, and the chromium content ω[Cr second phase test] was 14.9%; In step (six), substitute the formula and calculate: Formula 8: W[lime reduction]=2.14×{1.37%+(17%-14.9%)×56.1×70%÷86.34}÷93%×2.2×86.34-5.73-2.29-32%×0.8; calculated: W[lime reduction]=1.89 tons; The amount of lime added during the reduction period W [lime reduction] is 1.89 tons; The amount of fluorite added is (W[lime phase I]+W[lime phase II]+W[lime reduction])×25%=(5.73+2.29+1.89)×25%; calculated: the amount of fluorite added is 2.48 tons; Formula 9: W[ferromanganese alloy]=(0.4%-0.09%)×86.34÷99%÷65%; calculated: W[ferromanganese alloy]=0.42 tons; Formula 10: W[ferrosilicon alloy]=(17%-14.9%)×56.1+(0.35%-0.02%)×86.34÷75%÷70%; calculated: W[ferrosilicon alloy]=1.72 tons; The amount of ferromanganese alloy added W[ferromanganese alloy] is 0.42 tons, and the amount of ferrosilicon alloy added W[ferrosilicon alloy] is 1.72 tons; The molten steel was stirred by blowing argon gas from the bottom, and the reduction time was 10 minutes; sampling and testing, the carbon content ω[C reduction] of the molten steel after reduction was measured to be 0.035%, the silicon content ω[Si reduction] was 0.36%, the manganese content ω[Mn reduction] was 0.39%, and the chromium content ω[Cr reduction] was 17.01%, and the molten steel was poured into a ladle; In step (seven): After adding calcium wire into the ladle, sampling and testing were carried out, and the carbon content ω[C finished product detection] of the finished molten steel was 0.038%, the silicon content ω[Si finished product detection] was 0.35%, the manganese content ω[Mn finished product detection] was 0.38%, the chromium content ω[Cr finished product detection] was 16.99%, the phosphorus content ω[P finished product detection] was 0.021%, and the sulfur content ω[S finished product detection] was 0.003%. The ladle was connected to argon gas for soft blowing, and the soft blowing time was 13 minutes, and the smelting was completed.
[0015] In the above steps, the deviation value of the carbon content target value ω[C1st phase target] of the first-phase blowing molten steel and the carbon content detection value ω[C1st phase detection] of the first-phase blowing molten steel is 0%, which meets the deviation value range requirement of 0% to ±0.05%; the deviation value of the carbon content target value ω[C2nd phase target] of the second-phase blowing molten steel and the carbon content detection value ω[C2nd phase detection] of the second-phase blowing molten steel is 0%, which meets the deviation value range requirement of 0% to ±0.005%; the content of each element component of the finished molten steel product detection is within the steel grade parameter range required by the customer. Embodiment 3:
[0016] The parameters of stainless steel required by the customer are: C: 0.03%-0.05%, Si: 0.2%-0.5%, Mn: 0.3%-0.5%, P: 0%-0.035%, S: 0-0.006%, Cr: 16%-18%.
[0017] The production method of using chromite and recovered converter dust to smelt stainless steel liquid is carried out according to the above steps, wherein: In step (a): After testing, the weight percentage of the components of the converter dust ash powder is: Fe: 25%, calcium oxide: 20%, carbon content ω[C dust ash] is 8%, chromium content ω[Cr dust ash] is 16%, silicon content ω[Si dust ash] is 1.5%, and the balance is inevitable impurities; the chromium component recovery rate ε[Cr dust ash] in the converter dust ash powder is 80%; The block size of the chromite is 20mm-80mm. After testing, the weight percentage of its components is as follows: iron content is 30%, chromium content ω[Cr chromite] is 45%, carbon content ω[C chromite] is 8%, silicon content ω[Si chromite] is 5%; the chromium component recovery rate ε[Cr chromite] in the chromite is 90%; After testing, the block size of the high carbon ferrochrome is 20mm-80mm, and the weight percentage of its components is: iron content 30%, chromium content ω[Cr high carbon ferrochrome] is 55%, carbon content ω[C high carbon ferrochrome] is 8%, silicon content ω[Si high carbon ferrochrome] is 6%, manganese content ω[Mn high carbon ferrochrome] is 0.4%, and the remainder is inevitable impurities; the total addition amount of the high carbon ferrochrome is W[high carbon ferrochrome], and the chromium component recovery rate ε[Cr high carbon ferrochrome] in the high carbon ferrochrome is 95%; The block size of the ferrosilicon alloy is 20 mm-80 mm. After testing, the silicon content ω[Si ferrosilicon] of the ferrosilicon alloy is 75%, and the silicon component yield ε[Si ferrosilicon] in the ferrosilicon alloy is 75%; The block size of the ferromanganese alloy is 20 mm to 80 mm. After testing, the manganese content ω [Mn ferromanganese] of the ferromanganese alloy is 68%, and the manganese component recovery rate ε [Mn ferromanganese] in the ferromanganese alloy is 99%; After testing, the effective calcium oxide content ω[CaO dolomite] of the dolomite is 32%; the effective calcium oxide content ω[CaO lime] of the lime is 93%; According to the customer's requirements for stainless steel grades, the chromium content ω[Cr finished product] of the produced stainless steel grade is set to 18%, the carbon content ω[C finished product] is set to 0.05%, the silicon content ω[Si finished product] is set to 0.5%, the manganese content ω[Mn finished product] is set to 0.5%, the phosphorus content ω[P finished product] does not exceed 0.035%, and the sulfur content ω[S finished product] does not exceed 0.005%; the slag basicity value R is 2.2; at the same time, the weight of the produced stainless steel molten steel is set to W[molten steel], the carbon content in the stainless steel molten steel is set to ω[C molten steel], and the silicon content is set to ω[Si molten steel]; In step (ii): After testing, the phosphorus content of the dephosphorized molten iron is 0.01%, the sulfur content is 0.01%, the silicon content ω[Si molten iron] is 0%, the chromium content ω[Cr molten iron] is 0%, and the carbon content ω[C molten iron] is 3.2%; the amount of the dephosphorized molten iron added W[molten iron] is 60 tons, the amount of the converter dust ash powder added W[dust ash] is 2 tons, and the amount of chromite added W[chromite] is 2 tons; W[dust ash]: W[chromite]: W[molten iron] is 1:1:30; In step (3), substitute the formula and calculate: Formula 1: 18%×W[molten steel]=2×16%×80%+2×45%×90%+W[high carbon ferrochrome]×55%×95%+60×0; Formula 2: W[molten steel]=60+2+2+W[high carbon ferrochrome]; Calculation: W [high carbon ferrochrome] = 30.52 tons; W [molten steel] = 94.52 tons; Formula 3: ω[C molten steel] = (2×8%+2×8%+30.52×8%+60×3.2%) ÷ 94.52; calculated: ω[C molten steel] = 4.95%; Formula 4: ω[Si molten steel]=(2×1.5%+2×5%+30.52×6%+60×0)÷94.52; calculated: ω[Si molten steel]=2.07%; The weight of the stainless steel molten steel W[molten steel] is 94.52 tons, ω[molten steel] is 4.95%, ω[molten steel] is 2.07%; the total amount of high carbon ferrochrome added W[high carbon ferrochrome] is 30.52 tons; The carbon content target ω[C1st phase target] of the first phase blowing molten steel is set to 0.35%, and the oxygen utilization rate η[1st phase] of the first phase blowing is set to 65%; substitute into the formula and calculate: Formula 5: V[oxygen phase I] = (4.95% - 0.35%) × 94.52 × 1000 × 0.933 ÷ 65% + 2.07% × 0.8 × 94.52 × 1000; calculated: V[oxygen phase I] = 7806.19 cubic meters; The amount of dolomite added W [dolomite] is 0.8 tons; substitute into the formula and calculate: Formula 6: W[lime phase I] = 2.14 × 2.07% ÷ 93% × 2.2 × 94.52-32% × 0.8; calculated: W[lime phase I] = 9.65 tons; The amount of oxygen V[oxygen phase I] required for the first phase of blowing is 7806.19 cubic meters; the total amount of lime added in the first phase of blowing W[lime phase I] is 9.65 tons; In step (iv), During blowing at the first oxygen lance position, the oxygen blowing volume at the first oxygen lance position was 468.37 cubic meters, the amount of high carbon ferrochrome added was 4.58 tons, and the amount of lime added was 1.45 tons; When the second oxygen lance was used for blowing, the oxygen blowing volume of the second oxygen lance was 3122.48 cubic meters, the high carbon ferrochrome added was 15.26 tons, and the lime added was 4.83 tons; When the third oxygen lance position was used for blowing, the oxygen blowing volume of the third oxygen lance position was 2341.86 cubic meters, the amount of high carbon ferrochrome added was 10.68 tons, and the amount of lime added was 3.38 tons; When the fourth oxygen lance position is blowing, the oxygen blowing volume of the fourth oxygen lance position is 1248.99 cubic meters; When the fifth oxygen lance position is blowing, the oxygen blowing volume of the fifth oxygen lance position is 624.5 cubic meters; After the blowing was completed, samples were taken for testing, and the carbon content of the first-stage blowing molten steel was measured to be 0.34% [C first-stage test]. In step (V): The amount of lime added in the second phase blowing is W[lime second phase]=W[lime first phase]×40%=9.65×40%; calculated: W[lime second phase]=3.86 tons; Set the carbon content target ω[C2nd phase target] of the second phase blowing molten steel to 0.04% and the oxygen utilization rate η[2nd phase] of the second phase blowing to 20%; substitute into the formula and calculate: Formula 7: V[oxygen phase II] = (0.34% - 0.04%) × 94.52 × 1000 × 0.933 ÷ 20%; calculated: V[oxygen phase II] = 1322.81 cubic meters; The amount of oxygen V[oxygen phase II] required for the second phase blowing is 1322.81 cubic meters; After the blowing was completed, samples were taken for testing, and the carbon content ω[C second phase test] of the second phase blowing molten steel was 0.042%, the silicon content ω[Si second phase test] was 0.03%, the manganese content ω[Mn second phase test] was 0.12%, and the chromium content ω[Cr second phase test] was 16%; In step (six), substitute the formula and calculate: Formula 8: W[lime reduction]=2.14×{2.07%+(18%-16%)×56.1×75%÷94.52}÷93%×2.2×94.52-9.65-3.86-32%×0.8; calculated: W[lime reduction]=0.4 tons; The amount of lime added during the reduction period W [lime reduction] is 0.4 tons; The amount of fluorite added is (W[lime phase I]+W[lime phase II]+W[lime reduction])×25%=(9.65+3.86+0.4)×25%; calculated, the amount of fluorite added is 3.48 tons; Formula 9: W[ferromanganese alloy]=(0.5%-0.12%)×94.52÷99%÷68%; calculated: W[ferromanganese alloy]=0.53 tons; Formula 10: W[ferrosilicon alloy] = (18%-16%) × 56.1 + (0.5%-0.03%) × 94.52 ÷ 75% ÷ 75% = 1.91 tons; The amount of ferromanganese alloy added W[ferromanganese alloy] is 0.53 tons, and the amount of ferrosilicon alloy added W[ferrosilicon alloy] is 1.91 tons; The molten steel was stirred by blowing argon gas from the bottom, and the reduction time was 10 minutes; sampling and testing were performed, and the carbon content ω[C reduction] of the molten steel after reduction was measured to be 0.045%, the silicon content ω[Si reduction] to be 0.49%, the manganese content ω[Mn reduction] to be 0.49%, and the chromium content ω[Cr reduction] to be 17.98%, and the molten steel was poured into a ladle; In step (seven): After adding calcium wire into the ladle, sampling and testing were carried out, and the carbon content ω[C finished product detection] of the finished molten steel was measured to be 0.048%, the silicon content ω[Si finished product detection] was 0.47%, the manganese content ω[Mn finished product detection] was 0.48%, the chromium content ω[Cr finished product detection] was 17.97%, the phosphorus content ω[P finished product detection] was 0.022%, and the sulfur content ω[S finished product detection] was 0.003%. The ladle was connected to argon gas for soft blowing, and the soft blowing time was 15 minutes, and the smelting was completed.
[0018] In the above steps, the deviation value of the carbon content target value ω[C1st phase target] of the first-phase blowing molten steel and the carbon content detection value ω[C1st phase detection] of the first-phase blowing molten steel is -0.01%, which meets the deviation value range requirement of 0% to ±0.05%; the deviation value of the carbon content target value ω[C2nd phase target] of the second-phase blowing molten steel and the carbon content detection value ω[C2nd phase detection] of the second-phase blowing molten steel is 0.002%, which meets the deviation value range requirement of 0% to ±0.005%; the content of each element component of the finished molten steel product detection is within the steel grade parameter range required by the customer.
Claims
1. A production method for smelting stainless steel by using chromite ore and recovered converter dust, characterized in that: The following steps are included:
1. Preparation of raw materials before production and setting of content indicators for the production of stainless steel liquid: sampling of converter dust powder, chromite, high carbon ferrochrome, ferrosilicon alloy, ferromanganese alloy, lime and dolomite to be used for testing and preparation; The converter dust removal ash powder is the converter dust removal ash powder directly collected by the converter dust removal system during the converter smelting process; the carbon content of the converter dust removal ash powder is measured to be ω[C dust removal ash], the chromium content is ω[Cr dust removal ash], the silicon content is ω[Si dust removal ash], and the chromium component recovery rate in the converter dust removal ash powder is ε[Cr dust removal ash]; The block size of the chromite is required to be 20 mm-80 mm; the chromium content of the chromite is measured to be ω[Cr chromite], the carbon content is ω[C chromite], the silicon content is ω[Si chromite], and the chromium component recovery rate in the chromite is ε[Cr chromite]; The block size of the high carbon ferrochrome is required to be 20 mm-80 mm; the chromium content of the high carbon ferrochrome is measured to be ω[Cr high carbon ferrochrome], the carbon content is ω[C high carbon ferrochrome], the silicon content is ω[Si high carbon ferrochrome], and the manganese content is ω[Mn high carbon ferrochrome]; the total addition amount of the high carbon ferrochrome is W[high carbon ferrochrome], and the chromium component recovery rate in the high carbon ferrochrome is ε[Cr high carbon ferrochrome]; The block size of the ferrosilicon alloy is required to be 20 mm-80 mm; the silicon content of the ferrosilicon alloy is measured to be ω[Si ferrosilicon], and the silicon component yield in the ferrosilicon alloy is ε[Si ferrosilicon]; The block size of the ferromanganese alloy is required to be 20 mm-80 mm; the manganese content of the ferromanganese alloy is measured to be ω[Mn ferromanganese], and the manganese component yield in the ferromanganese alloy is ε[Mn ferromanganese]; The effective calcium oxide content of the dolomite is ω[CaO dolomite]; the effective calcium oxide content of the lime is ω[CaO lime]; According to the customer's requirements for stainless steel grades, the chromium content of the finished stainless steel grades is set to ω[finished Cr], the carbon content is ω[finished C], the silicon content is ω[finished Si], the manganese content is ω[finished Mn], the phosphorus content is ω[finished P], and the sulfur content is ω[finished S]; the basicity value of the slag is R; (ii) Adding steel: using a hopper to pour the converter dust powder into the converter, then adding dephosphorized hot metal, and then adding chromite into the converter through a silo; the phosphorus content in the dephosphorized hot metal is ≤0.015%, and the sulfur content is ≤0.04%. The chromium content of the dephosphorized hot metal is measured to be ω[Cr hot metal], the silicon content is ω[Si hot metal], and the carbon content is ω[C hot metal]; the amount of the dephosphorized hot metal added is W[hot metal], the amount of the converter dust powder added is W[dust ash], and the amount of chromite added is W[chromite]; the weight ratio of the converter dust powder added, the chromite added, and the dephosphorized hot metal added is 1:1:(25-30); (III) Pre-calculation: The weight of the stainless steel molten steel produced is set as W[molten steel], and the weight of the stainless steel molten steel produced W[molten steel] is the sum of the amount of dephosphorized molten iron added W[molten iron], the amount of converter dust powder added W[dust ash], the amount of chromite added W[chromite] and the amount of high carbon ferrochrome added W[high carbon ferrochrome]; the carbon content in the stainless steel molten steel is set as ω[C molten steel], and the silicon content is set as ω[Si molten steel]; The weight W[molten steel] of the produced stainless steel molten steel, the total amount of high carbon ferrochrome added W[high carbon ferrochrome], the carbon content ω[C molten steel] and the silicon content ω[Si molten steel] in the stainless steel molten steel are calculated according to the following formulas: ω[Cr finished product]×W[molten steel]=W[dust removal ash]×ω[Cr dust removal ash]×ε[Cr dust removal ash]+W[chromite]×ω[Cr chromite]×ε[Cr chromite]+W[high carbon ferrochrome]×ω[Cr high carbon ferrochrome]×ε[Cr high carbon ferrochrome]+W[molten iron]×ω[Cr molten iron]; W[molten steel]=W[molten iron]+W[dust ash]+W[chromite]+W[high carbon ferrochrome]; ω[Cmolten steel] = (W[dust ash] × ω[Cdust ash] + W[chromite] × ω[Cchromite] + W[high carbon ferrochrome] × ω[Chigh carbon ferrochrome] + W[molten iron] × ω[Cmolten iron]) ÷ W[molten steel]; ω[Si molten steel] = (W[dust ash] × ω[Si dust ash] + W[chromite] × ω[Si chromite] + W[high carbon ferrochrome] × ω[Si high carbon ferrochrome] + W[molten iron] × ω[Si molten iron]) ÷ W[molten steel]; The carbon content target of the first-phase blowing molten steel is set to ω[C first-phase target], the amount of oxygen required for the first-phase blowing is set to V[oxygen first-phase], and the oxygen utilization rate of the first-phase blowing is set to η[first-phase]. The amount of oxygen required for the first-phase blowing V[oxygen first-phase] is calculated according to the following formula: V[oxygen phase I] = (ω[C molten steel] - ω[C phase I target]) × W[molten steel] × 1000 × 0.933 ÷ η[phase I] + ω[Si molten steel] × 0.8 × W[molten steel] × 1000; The amount of dolomite added is W[dolomite], W[dolomite] is 0.8 tons; the total amount of lime added in the first stage of blowing is set to W[lime first stage]; The total amount of lime added in the first stage of blowing W[lime first stage] is calculated according to the following formula: W[lime phase I] = 2.14 × ω[Si molten steel] ÷ ω[CaO lime] × R × W[molten steel] - ω[CaO dolomite] × W[dolomite]; (IV) First-stage blowing: The first-stage blowing is started by top-bottom combined blowing. During the blowing process, high-carbon ferrochrome and lime are added into the furnace in batches through the silo, and the dephosphorized molten iron is blown at five oxygen lance positions: During blowing at the first oxygen lance position, 0.8 tons of dolomite is added through the silo; the oxygen blowing amount at the first oxygen lance position is 6% of the oxygen amount V[oxygen phase I] required for the first phase of blowing; the high carbon ferrochrome added at the first oxygen lance position is 15% of the total amount of high carbon ferrochrome added W[high carbon ferrochrome]; the lime added at the first oxygen lance position is 15% of the total amount of lime added in the first phase of blowing W[lime phase I]; During blowing at the second oxygen lance position, the oxygen blowing amount at the second oxygen lance position is 40% of the oxygen amount V[oxygen phase I] required for the first phase blowing, the high carbon ferrochrome added at the second oxygen lance position is 50% of the total high carbon ferrochrome added W[high carbon ferrochrome], and the lime added at the second oxygen lance position is 50% of the total lime added in the first phase blowing W[lime phase I]; During blowing at the third oxygen lance position, the oxygen blowing amount at the third oxygen lance position is 30% of the oxygen amount V[oxygen phase I] required for the first phase of blowing, the high carbon ferrochrome added at the third oxygen lance position is 35% of the total high carbon ferrochrome added W[high carbon ferrochrome], and the lime added at the third oxygen lance position is 35% of the total lime added in the first phase of blowing W[lime phase I]; When the fourth oxygen lance is used for blowing, the oxygen blowing amount of the fourth oxygen lance is 16% of the oxygen amount V[oxygen first phase] required for the first phase of blowing; When the fifth oxygen lance is used for blowing, the oxygen blowing amount of the fifth oxygen lance is 8% of the oxygen amount V[oxygen first phase] required for the first phase of blowing; After the blowing is completed, samples are taken for testing, and the carbon content of the first-stage blowing molten steel is measured to be ω[C first-stage test]; (V) Second stage blowing: The second stage blowing is carried out by bottom lance blowing, and lime is added. The amount of lime added in the second stage blowing is W[lime second stage], and the amount of lime added in the second stage blowing W[lime second stage] is 40% of the total amount of lime added in the first stage blowing W[lime first stage], the amount of oxygen required for the second stage blowing is set to V[oxygen second stage], the oxygen utilization rate of the second stage blowing is set to η[second stage], and the carbon content target of the molten steel in the second stage blowing is set to ω[C second stage target]; The amount of oxygen V[oxygen phase II] required for the second phase blowing is calculated according to the following formula: V[oxygen phase II] = (ω[C phase I detection] - ω[C phase II target]) × W[molten steel] × 1000 × 0.933 ÷ η[phase II]; After the blowing is completed, samples are taken for testing, and the carbon content of the second-stage blowing molten steel is measured as ω [C second-stage test], the silicon content is ω [Si second-stage test], the manganese content is ω [Mn second-stage test], and the chromium content is ω [Cr second-stage test]; (VI) Reduction and tapping: During the reduction period, lime, fluorite, ferrosilicon alloy and ferromanganese alloy are added; the amount of lime added during the reduction period is W[lime reduction]; the amount of fluorite added is 25% of the total amount of lime added in the first stage of blowing W[lime first stage], the amount of lime added in the second stage of blowing W[lime second stage], and the amount of lime added in the reduction period W[lime reduction]; the amount of ferrosilicon alloy added is W[ferrosilicon alloy], and the amount of ferromanganese alloy added is W[ferromanganese alloy]; The amount of lime added during the reduction period W[lime reduction], the amount of ferromanganese alloy added W[ferromanganese alloy] and the amount of ferrosilicon alloy added W[ferrosilicon alloy] are calculated according to the following formula: W[lime reduction]=2.14×{ω[Si molten steel]+(ω[finished Cr product]-ω[Cr second phase detection])×56.1×ω[Si ferrosilicon]÷W[molten steel]}÷ω[CaO lime]×R×W[molten steel]-W[lime first phase]-W[lime second phase]-ω[CaO dolomite]×W[dolomite]; W[ferromanganese alloy]=(ω[Mn finished product]-ω[Mn second-stage test])×W[molten steel]÷ε[Mn ferromanganese]÷ω[Mn ferromanganese]; W[ferrosilicon alloy]=(ω[finished Cr product]-ω[secondary Cr test])×56.1+(ω[finished Si product]-ω[secondary Si test])×W[molten steel]÷ε[Si ferrosilicon]÷ω[Si ferrosilicon]; The molten steel is stirred by blowing argon gas from the bottom, and the reduction time is controlled to be 10 minutes; sampling is performed for testing, and the carbon content of the molten steel after reduction is measured to be ω [C reduction], the silicon content is ω [Si reduction], the manganese content is ω [Mn reduction], and the chromium content is ω [Cr reduction], and the molten steel is poured into a ladle; (VII) Refining: The ladle enters the refining furnace, and under the action of the electrode, 400kg of lime, 200kg of fluorite and 40kg of ferrosilicon powder are added to adjust the slag and temperature; Use a wire feeder to add 150 meters of calcium wire into the ladle, take samples for testing, and measure the carbon content of the finished molten steel to be ω [C finished product test], silicon content to be ω [Si finished product test], manganese content to be ω [Mn finished product test], chromium content to be ω [Cr finished product test], phosphorus content to be ω [P finished product test], and sulfur content to be ω [S finished product test]; connect the ladle with argon gas for soft blowing, and the soft blowing time is controlled within 10-15 minutes; after the soft blowing is completed, the ladle enters the continuous casting process, and the smelting of molten steel is completed.